Intrathoracic gossypiboma. (8th January 2014) - Hameed, Aamir; Naeem, Ayesha; Azhar, Maimoona; Fatimi, Saulat Husnain
Abstract : Gossypiboma refers to retained sponge or swab in any body cavity after surgery. Although it is a rare occurence, it can lead to various complications which include adhesions, abscess formation and subsequent infections. Gossypiboma occurs as a result of not using radio-opaque sponges, poorly performed sponge counts, inadequate wound explorations on suspicion and misread intraoperative radiographs. Therefore, this event can be avoided if strict preventive measures are taken. Moreover, further complications can be avoided following the correct and early diagnosis of gossypiboma. Gossypiboma is an important topic as it carries great medicolegal consequences for the surgeon. We have presented three cases of intrathoracic gossipiboma following previous cardiothoracic surgeries. They presented years after their surgeries, with features varying from patient to patient, ranging from cough and fever to no sypmtoms at all. CT scan only showed a mass lesion in all cases, therefore we proceeded for CT-guided biopsy which was also found to be inconclusive. It was only after entering the thoracic cavity via video-assisted thoracoscopy/thoracotomy that the diagnosis was made and sponges were taken out successfully. All our cases recovered with no further complications.